(untitled) (Annals of Medical Research, 2021)
Aim: Poisoning cases have a significant place among childhood health problems in terms of morbidity and mortality. Cases involving children younger than five years of age constitute the most common poisoning cases that are caused by accidents or injuries. In this study, we attempted to determine the possible precautions by analyzing the age distribution in childhood poisoning cases.Material and Methods: The files of poisoning cases applying to the pediatric emergency service unit of the hospital between March 2018 and March 2019 have been retrospectively analyzed. Cases have been analyzed in terms of patients’ age, sex and nationality and also in terms of causes of poisoning and pharmacological agents that cause poisoning.Results: 120 poisoning cases admitted to emergency service throughout one-year period comprised 0.4% of all (24,942) applications. 57 of the patients (47.5%) were female while 63 (52.5%) were male. The youngest of the patients was 0-year-old and the oldest was 17 years old and the average age of the patients was 5.2±5.5. Poisoning cases were most frequently seen (70,8%) in children in 0-5 age range and male patients comprised the majority of them. The most common cause of poisoning was paracetamol and antipyretic type of medicines. Others were organophosphate (19.4%), rat poison (12.9%) and other substances (antipsychotics, antibiotics and vitamins) (8.1%) and caustic substances (6.7%). Conclusion: Most of the poisoning cases were caused by medicines that were left out in the open. We think such cases can be reduced through parent education.